Desenvolvimento neuropsicomotor e qualidade de vida de bebês prematuros nos primeiros seis meses de vida - Marques, Alice Stedile; Dalpiaz, Jaíne Scariot (My University, 2024)
Objective: to evaluate the neuropsychomotor development (DNPM) and quality of life of premature infants in the first six months of life, comparing children from different socioeconomic backgrounds. Method: this is an observational, analytical, cross-sectional study. The study included 40 preterm infants aged 3 to 6 months, born weighing less than 2,500g. The infants were equally divided into two groups: infants from the SUS group (GSUS), registered at the High-Risk Outpatient Clinic of the Clinical Center of the University of Caxias do Sul (CECLIN-UCS), and infants from the private healthcare group (GPAR), evaluated in a private practice setting. To assess the neuropsychomotor development of the infants, the Bayley III scale was administered, along with four other questionnaires: PedsQL, AHEMD-IS, ABEP, and an identification questionnaire. These instruments aimed to evaluate, respectively, quality of life, the opportunities that the home environment and family provide for the infant's motor development, family economic status, and biological and environmental variables. Descriptive statistics, independent t-test, Mann-Whitney U test, Chi square test, and Fisher's Exact test were used (p<0.05). Results: No significant differences were observed in DNPM. Results: No significant differences were observed in DNPM (Cognitive: p=0.13; Language: p=0.13; Motor: p=0.15) and quality of life (p=0.27) among premature infants comparing GSUS and GPAR. However, poorer performance indices were observed in infants from GSUS. The main differences between groups were observed for environmental variables (Mother's age: p=0.02; Number of siblings: p=0.01; Number of prenatal consultations: p=0.002; Father's education: p=0.000; Mother's education: p=0.000; Family income: p=0.000). Conclusion: Environmental factors appear to have a lesser impact on neuropsychomotor development of infants in this age group. This may be due to the extended hospitalization period limiting interaction with family and exposure to household stimuli. [resumo fornecido pelos autores]
Objetivo: avaliar o desenvolvimento neuropsicomotor (DNPM) e qualidade de vida (QV) de prematuros nos primeiros seis meses de vida, comparando crianças de diferentes contextos socioeconômicos. Método: trata-se de um estudo observacional, analítico e transversal. Participaram do estudo 40 bebês pré-termo com idade corrigida de 3 a 6 meses, nascidos com peso abaixo de 2.500g. Os bebês foram divididos igualmente em dois grupos: os bebês do grupo SUS (GSUS), cadastrados no Ambulatório de Alto Risco do Centro Clínico da Universidade de Caxias do Sul (CECLIN-UCS), e os bebês do grupo particular (GPAR), avaliados em um consultório particular. Para avaliar o DNPM dos bebês, foi aplicada a escala Bayley III, além de outros quatro questionários: PedsQL, AHEMD-IS, ABEP e um questionário de identificação. Esses instrumentos visam avaliar, respectivamente, a QV, as oportunidades que o ambiente domiciliar e a família proporcionam ao desenvolvimento motor do bebê, a situação econômica da família e as variáveis biológicas e ambientais. Foi utilizada estatística descritiva, Teste t independente, Teste U de Mann Whitney, Teste Qui-Quadrado e Exato de Fisher, (p<0,05). Resultados: Não foram observadas diferenças significativas no DNPM (Cognitivo: p=0,13; Linguagem: p=0,13; Motor: p=0,15) e na QV (p=0,27) dos bebês prematuros comparando GSUS e GPAR. No entanto, os piores índices de desempenhos foram observados nos bebês do GSUS. As principais diferenças entre os grupos foram observadas para as variáveis ambientais (Idade da mãe: p=0,02; Número de irmãos: p=0,01; Número de consultas pré-natal: p=0,002; Escolaridade do pai: p=0,000; Escolaridade da mãe: p=0,000; Renda familiar: p=0,000). Conclusão: Os fatores ambientais parecem ter um impacto menor no DNPM dos bebês nesta faixa etária. Isso porque o longo período de hospitalização limita a interação com a família e a exposição aos estímulos do ambiente doméstico. [resumo fornecido pelos autores]
Keywords: Fisioterapia; Crianças - Desenvolvimento; Qualidade de vida; Prematuros